N-SO3H functionalised brønsted acidic ionic liquid catalysed sequential one-pot synthesis of 2-amino-3-cyanopyridines via claisen-schmidt condensation under solvent-free condition - Das, Sukanya; Paul, Subham; Kashyap, Niharika; Saikia, Pinku; Borah, Ruli (Chemistryselect, 2024)
This work presents a simple approach for the synthesis of 2-amino-3-cyanopyridines via a one pot two-step sequential route catalysed by direct N–SO3H functionalised Br & oslash;nsted acidic ionic liquids (BAILs). Herein, catalytic activities of four BAILs namely ([TSPi][Cl](2), [DSIM][TFA], [EDSIM][TFA] and [DBDSA][TFA]) were explored and among them [TSPi][Cl](2) was found to be the most efficient reusable homogeneous catalyst. This process involves the ionic liquid catalysed in situ generation of chalcones from Claisen-Schmidt condensation between aromatic aldehydes and acetophenone/4-Cl acetophenone, followed by multicomponent reaction (MCR) with malononitrile and ammonium acetate using the same IL catalyst to selectively produce 2-amino-3-cyanopyridine derivatives in a solvent-free medium at 80 degrees C within 30-60 minutes in high yields (96-86 %). This amalgamation of MCR with ionic liquids and solvent-free conditions makes the present work more compliant with the protocols of Green Chemistry.
Keywords: 2-amino-3-cyanopyridines; Bronsted acidic ionic liquids; chalcones; Multicomponent reaction; One-pot approach